A Network of Networks : Supporting Good Practice in Network Leadership and the Dissemination of Good Practice in Tertiary Education : final report. - Keppell, Mike; Suddaby, Gordon; Hard, Natasha (Office for Learning and Teaching, 2014)
The National Networking Initiative (NNI) focuses on developing a comprehensive network for disseminating, promoting, and enhancing the outcomes of ALTC/DEEWR funded projects. The project is led by ACODE and ascilite. The aim of the NNI is to continue ALTC's critical roles of: facilitating the sharing of best practice, promoting collaboration and collegiality, and continuing to engage academic staff in the scholarship of learning and teaching. The projects outcomes will include: developing a sustainable network higher education organizations to progress the dissemination, promotion and enhancement of 'best practice' in higher education learning and teaching. These 'kindred' higher education organizations: ACODE, ascilite, Herdsa, CADAD, ODLAA together with Netspot and AARNet are critical in developing the strategy that will guide NNI. The project leaders will facilitate the networked-organizations to support the NNI goal of disseminating research on the scholarship of learning and teaching, and communicating strategies, and best practice outcomes from exemplar ALTC projects. The NNI will also establish collaborative relationships with the Promoting Excellence Networks (PEN's) to support and enhance higher education learning and teaching. A second outcome of the NNI focuses on disseminating, promoting, and enhancing the outcomes of the 'Good Practice Reports' (GPRs) through seminars, workshops and existing conferences and activities of the networked-organizations.